Pedal power drives Laos net dreams - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Pedal power drives Laos net dreams: bicycle-powered PCs should get remote villages online , BBC East Asia Today, 21 November 2002